Picturing Frederick Douglass an illustrated biography of the nineteenth century's most photographed American - Stauffer, John 1965-; Trodd, Zoe; Bernier, Celeste-Marie 1975- (Liveright Publishing Corporation, 2015)
Part I. The photographs -- Part II. Contemporaneous artwork -- Part III. The photographic legacy -- Part IV. Douglass's writings on photography -- Part V. Catalogue raisonné
Literaturverzeichnis: Seiten 241-251
"With an Epilogue by Henry Louis Gates, Jr., and an Afterword by Kenneth B. Morris, Jr." -- dust jacket. - Includes bibliographical references (pages 241-251) and index
Keywords: Douglass, Frederick -- 1818-1895; Fotografie; Douglass, Frederick / 1818-1895; Douglass, Frederick / 1818-1895 / Pictorial works; Douglass, Frederick 1818-1895; Douglass, Frederick 1818-1895 / Pictorial works; Abolitionists / United States / Biography; African American abolitionists / Biography; Abolitionists / Biography / United States; Biografie